Evaluation of posterior airway space after setback surgery by simulation. - Karan, Nazife Begum; Kahraman, Sevil (Medical & Biological Engineering & Computing, 2019)
The possible negative outcomes of mandibular setback surgery (MSS) on the upper airway (UA) have become an important issue in recent years. The purpose of the present study was to compare the different amounts of MSS and to confirm the accepted maximum amount of mandibular setback by using Computational Fluid Dynamics (CFD) method. An anatomically similar UA model was constructed from magnetic resonance images of a systemically healthy individual. Two out of six models were kept as control models and the remaining four models were created to represent MSS scenarios with different amounts to correct Class III skeletal abnormality. The airflow was assumed laminar, incompressible, and the surrounding soft tissue was assumed to be linear elastic. The sixth model that was representative of 15 mm of MSS showed statistically significant differences from the other models (p < 0.05). No significant differences were observed among other models in terms of all the parameters (p > 0.05). CFD has been recently used in researches by modeling the UA flow; however, to the best of our knowledge, none of the studies have proved the maximum limits of MSS amounts with this technique. Graphical abstract ᅟ.